Significantly lower anti-Leishmania IgG responses in Sudanese versus Indian visceral leishmaniasis. - Tapan Bhattacharyya; Duncan E Bowes; Sayda El-Safi; Shyam Sundar; Andrew K Falconar; Om Prakash Singh; Rajiv Kumar; Osman Ahmed; Marleen Boelaert; Michael A Miles (Public Library of Science (PLoS), 2014)
BACKGROUND: Visceral leishmaniasis (VL), a widely distributed systemic disease caused by infection with the Leishmania donovani complex (L. donovani and L. infantum), is almost always fatal if symptomatic and untreated. A rapid point-of-care diagnostic test for anti-Leishmania antibodies, the rK39-immunochromatographic test (rK39-ICT), has high sensitivity and specificity in South Asia but is less sensitive in East Africa. One of the underlying reasons may be continent-specific molecular diversity in the rK39 antigen within the L. donovani complex. However, a second reason may be differences in specific IgG anti-Leishmania levels in patients from different geographical regions, either due to variable antigenicity or immunological response. METHODOLOGY/PRINCIPAL FINDINGS: We determined IgG titres of Indian and Sudanese VL patients against whole cell lysates of Indian and Sudanese L. donovani strains. Indian VL patients had significantly higher IgG titres against both L. donovani strains compared to Sudanese VL patients (p<0.0001). Mean reciprocal log10 50% end-point titres (1/log10t50) were i) 3.80 and 3.88 for Indian plasma and ii) 2.13 and 2.09 for Sudanese plasma against Indian and Sudanese antigen respectively (p<0.0001). Overall, the Indian VL patients therefore showed a 46.8-61.7 -fold higher mean ELISA titre than the Sudanese VL patients. The higher IgG titres occurred in children (<16 years old) and adults of either sex from India (mean 1/log10t50: 3.60-4.15) versus Sudan (mean 1/log10t50: 1.88-2.54). The greatest difference in IgG responses was between male Indian and Sudanese VL patients of ≥ 16 years old (mean 1/log10t50: 4.15 versus 1.99 = 144-fold (p<0.0001). CONCLUSIONS/SIGNIFICANCE: Anti-Leishmania IgG responses among VL patients in Sudan were significantly lower than in India; this may be due to chronic malnutrition with Zn(2+) deficiency, or variable antigenicity and capacity to generate IgG responses to Leishmania antigens. Such differential anti-Leishmania IgG levels may contribute to lower sensitivity of the rK39-ICT in East Africa.